Control of dielectric surface energy by dry surface treatment for high performance organic thin film transistor based on dibenzothiopheno[6,5-b:6′,5′-f]thieno[3,2-b]thiophene semiconductor - Ajeong Choi (AIP Advances, 2020)
We studied organic thin film transistors using vacuum-deposited para-sexiphenyl (p-6P) as a sublayer to reduce the surface energy of the dielectric material. The correlation between the growth mode of a thin film of the organic semiconductor dibenzothiopheno[6,5-b:6′,5′-f]thieno[3,2-b]thiophene and the number of p-6P sublayers could be explained by a surface energy difference resulting from molecular orientation changes in the p-6P layer. A local surface energy difference was confirmed by measuring the adhesion force using a nanomechanical force measurement method.